Synchronous vasomotion of skin microvessels at acupoints on the twelve main meridians of beagle dogs. Issue 6 (17th June 2020) - Zhang, Tao; Liu, Chun; Hu, Ge; Dong, Hong; Mu, Xiang
Abstract: Background/purpose: Synchronous microvascular vasomotion was detected at acupoints in our previous human study. This present study aimed to characterize the skin microvascular vasomotion at acupoints on the twelve meridians of beagle dogs. Materials and methods: Two acupoints were selected on each meridian and exactly located at the rosy red spots by an electrochemical color‐appearing method, where the electrical resistance was measured. The skin blood flow at acupoints was recorded by laser Doppler flowmetry (LDF), and microvascular vasomotion was analyzed according to LDF waveforms. Results: The skin electrical resistance at acupoints was significantly lower than that at control non‐acupoints. The LDF waveforms at acupoints were sinusoidal, which showed the synchronization of the microvascular vasomotion. The spectral analysis revealed that the vasomotion frequencies at acupoints on the same meridian were identical but not among different meridians, and the frequencies on the twelve main meridians displayed a constant order. Conclusion: The skin microvascular vasomotion is synchronous at acupoints of beagle dogs and has a specific frequency along the meridian, and the electrochemical color‐appearing method is a feasible strategy for the precise and visual location of acupoints. The study provides evidence for the universality of synchronous vasomotion of skin microvessels at acupoints.